Radiocarbon dating redefines the timing and circumstances of the chicken’s introduction to Europe and northwest Africa - Best, J; Doherty, S; Armit, I; Cunliffe, B; Higham, T; Lebrasseur, O; Trentacoste, A; Larson, G (Cambridge University Press, 2022)
Astonishingly little is known about the early history of the chicken (Gallus gallus domesticus). To better understand their spatiotemporal spread across Eurasia and Africa, we radiocarbon dated presumed early chicken bones. The results indicate chickens were an Iron Age arrival to Europe and that there was a consistent time-lag of several centuries between their introduction to new regions and incorporation into the human diet. Well-dated evidence for Britain and mainland Europe suggests chickens were initially considered exotica and buried as individuals, were gradually incorporated into human funerary rites, and only much later came to be seen as just ‘food’.